Competing claims on disputed lands: The Complexity of Resource tenure in the Nicaragua interior - Nygren, Anja
This essay analyzes the complexity and contradiction of resource-tenure regimes on tropical forest frontiers by drawing on a case study carried out in the department of Río San Juan, southeasterns Nicaragua. The main attention is given to competing claims over productive resources ant to contradictory relationships between the modalities of resource control